MEMBUMIKAN ISLAM MODERAT: STUDI INTERNALISASI NILAI ISLAM MODERAT BAGI GENERASI MUDA: MEMBUMIKAN ISLAM MODERAT: STUDI INTERNALISASI NILAI ISLAM MODERAT BAGI GENERASI MUDA - Azmi, Muhammad Mursyidul; Zulfiana, Aliza Fitria (Raudhah - Proud To Be Professional, 2023)
Internalization is a process of appreciating and cultivating a teaching value so that it can become a reference in knowledge to be able to influence daily life. The focus of this research is (1) Forms of internalization of moderate Islamic values ??in the Al-Fattah Islamic boarding school. (2) The process of internalizing moderate Islamic values ??at the Al-Fattah Islamic boarding school. (3) Implications of internalizing moderate Islamic values ??in the Al-Fattah Islamic boarding school. This research uses a qualitative approach with a multi-case study type. Collecting data using interviews, observation, and documentation. Data analysis techniques using data reduction techniques, data presentation, and drawing conclusions. The results of this study are (1) the forms of values ??internalizing moderate Islam in the Al-Fattah Islamic boarding school are Tawazun, Tawasuth, Tasamuh, I'tidal, Shiddiq, As-Syura. (2) The process of internalizing moderate Islamic values ??at the Al-Fattah Islamic boarding school has 3 stages: Value Transformation, Value Transactions and Value Trans-Internalization. (3) Implications of Internalizing Moderate Islamic Values ??can have a significant positive impact, one of which is an increase in the sense of unity, oneness of the students, the emergence of a high sense of empathy and sympathy, reminding one another and respecting one another.